Kant, Global Politics and Cosmopolitan Law. A Reply to G. Geismann - Corradetti, Claudio (Con-Textos Kantianos. International Journal of Philosophy, 2023)
In this reply I rebut Mr Geismann’s unproved charges to my work on Kant’s cosmopolitanism. In my study I argue for a novel reading for the ‘world republic’ (Weltrepublik) in regulative terms. I defend also a non-perfectionist model of politics which for Kant brings us to a continuous normative striving for improvement. Unfortunately, Geismann has deliberately misunderstood the distinctive proposal I advance. The dismissive attitude towards my thesis reveals also discriminatory structural problem of certain Kantian conservative scholarship towards innovative proposals coming from academically not-aligned interpreters.